Knowledge, attitude and practice regarding needle stick injuries (NSI) among nursing students in faculty of medicine and health sciences, UNIMAS - Hu, Anna Tsing Tsing (Faculty of Medicine & Health Sciences, 2008)
Nursing students are at high risk of needlestick injury due to their limited clinical experience. The purpose of this paper is to explore the prevalence and causative of NSI, and knowledge, attitude and practice regarding needle stick injury among nursing students of Faculty Health and Medicine Sciences, Universiti of Malaysia Sarawak. A descriptive research design using questionnaires was done on 50 nursing students who were choosen by simple random sampling.